In Vitro Properties of Orthodontic Adhesives with Fluoride or Amorphous Calcium Phosphate - Clara Ka Wai Chow; Christine D. Wu; Carla A. Evans (International Journal of Dentistry)
This in vitro study evaluated the efficacy of orthodontic adhesives with fluoride or amorphous calcium phosphate (ACP) in reducing bacterial adhesion and enamel demineralization. Forty human premolars each sectioned buccolingually into three parts were bracketed with control resin (Transbond XT) or adhesives containing ACP (Aegis Ortho) or fluoride (QuickCure). Artificial lesions induced by pH cycling were examined by X-ray photoelectron spectrophotometry (XPS) and polarized light microscopy (PLM). After 28 days, Aegis Ortho demonstrated the lowest calcium and phosphorous content by XPS analysis. After 42 days, reductions in lesion depth areas were 23.6% for Quick Cure and 20.3% for Aegis Ortho (P<0.05). In the presence of 1% sucrose, adhesion of Streptococcus mutans to Aegis Ortho and Quick Cure was reduced by 41.8% and 37.7% (P<0.05) as compared to Transbond XT. Composites containing ACP or fluoride reduced bacterial adherence and lesion formation as compared to a composite without ACP or fluoride.